2016
DOI: 10.3174/ajnr.a4903
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia Severity Correlates with White Matter Degeneration in Spinocerebellar Ataxia Type 7

Abstract: BACKGROUND AND PURPOSE:There is a scarcity of information on the effect of white matter degeneration in patients with spinocerebellar ataxia type 7. Therefore, we investigated the WM integrity in a large group of patients with spinocerebellar ataxia type 7 by using Tract-Based Spatial Statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Similarly, the FA differed from the pFA by also being smaller in patients in almost every voxel of the cerebellar peduncles. Other studies using DTI to study SCA7 corroborated this, finding that the MD and FA were abnormal in the same regions we found the single-compartment MD and FA to be abnormal in 13, 19 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, the FA differed from the pFA by also being smaller in patients in almost every voxel of the cerebellar peduncles. Other studies using DTI to study SCA7 corroborated this, finding that the MD and FA were abnormal in the same regions we found the single-compartment MD and FA to be abnormal in 13, 19 .…”
Section: Discussionsupporting
confidence: 86%
“…[13][14][15][16] . DTI, which is typically used to assess WM microstructural integrity via measures of water diffusivity 17,18 , has detected microstructural abnormalities in the cerebellar WM, cerebellar peduncles, brainstem, cerebral peduncles, and several cerebral WM tracts including the internal and external capsules, corona radiata, optical radiation, corpus callosum, and miscellaneous temporal, occipital, parietal, and frontal WM in patients 13,19 . These abnormalities were indicated by both an increased mean diffusivity (MD), a measure of the magnitude of diffusion in all directions, and decreased fractional anisotropy (FA), a measure of how preferentially water diffuses in the principal direction of diffusion as compared to the other directions 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both the striatum and thalamus are part of the sensory-motor network, which was found to be altered in SCA7 patients [ 30 , 31 ], as well as in HD in correlation with the severity of motor symptoms [ 32 ]. In SCA7, correlations were found between ataxia severity score of patients and impairment of several white matter tracts, including the anterior thalamic radiation [ 33 ]. Thus, the vulnerability of thalamus and striatum may reflect ataxia severity in the SCA7 140Q/5Q model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed altered functional connectivity between the cerebellum and hippocampus or parahippocampal areas of patients, which may account for specific memory dysfunctions [ 4 , 30 , 33 ]. Interestingly, hippocampal neurons show accumulation of mATXN7 and alteration of short-term synaptic plasticity in SCA7 266Q/5Q mice [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has also been reported that gluten sensitivity can also be manifested without enteropathy (Aziz et al, 2012 ), rendering the diagnosis of such GA patients difficult. The symptoms of GA include gait ataxia, dysarthria, upper limb/lower limb ataxia, and ocular signs (Hernandez-Castillo et al, 2016 ). However, the onset of GA is usually not apparent, but it can rapidly progress, mimicking paraneoplastic cerebellar degeneration (Zis and Hadjivassiliou, 2019 ).…”
Section: Introductionmentioning
confidence: 99%